2021
DOI: 10.3390/brainsci11121636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraoperative Dexmedetomidine Infusion on Postoperative Pain after Craniotomy: A Narrative Review

Abstract: Craniotomy involves procedures with high incidences of postoperative pain. Dexmedetomidine, a highly selective a2-adrenoreceptor agonist, has been shown to be beneficial in neuroanaesthesia. The purpose of this narrative review was to assess the effect and safety of dexmedetomidine given intraoperatively during anaesthesia compared to placebo and demonstrate the effect on acute postoperative pain in adult patients undergoing craniotomy. Literature published from 1996 until 2021 were analysed through a search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
2
2
1
Order By: Relevance
“…Preoperative bodily pain may more strongly contribute to postoperative chronic pain than preoperative mental health; however, there was a weak relationship between bodily pain and mental health (Spearman's correlation coe cient was 0.37, p < 0.001). Some drugs, including dexmedetomidine and acetaminophen, decrease post-craniotomy pain (20,21), which was inconsistent with our results. This could be attributed to our small sample size.…”
Section: Resultscontrasting
confidence: 99%
“…Preoperative bodily pain may more strongly contribute to postoperative chronic pain than preoperative mental health; however, there was a weak relationship between bodily pain and mental health (Spearman's correlation coe cient was 0.37, p < 0.001). Some drugs, including dexmedetomidine and acetaminophen, decrease post-craniotomy pain (20,21), which was inconsistent with our results. This could be attributed to our small sample size.…”
Section: Resultscontrasting
confidence: 99%
“…Some drugs, including dexmedetomidine and acetaminophen, decrease post-craniotomy pain [ 19 , 20 ], which was inconsistent with our results. This could be attributed to our small sample size.…”
Section: Discussioncontrasting
confidence: 97%
“…Although we included only a small number of patients in our study, data analysis shows that a single dose of dexamethasone given at the time of induction reduces PONV after LC, which is comparable to other studies done in the past. It is not an expensive drug, and according to our results and other previous studies, it can be used regularly at the time of induction in LC, and it has been found more effective in preventing PONV than other anti-emetic drugs available (Neufeld, 2009;Shaheed, 2017;Syrous et al, 2021).…”
Section: Resultssupporting
confidence: 64%